Smoking and its effect on periodontium - Revisited - Gurparkash Singh Chahal; Kamalpreet Chhina; Vipin Chhabra; Amna Chahal (Wolters Kluwer Medknow Publications, 2017)
Cigarette smoking represents a major preventable cause of human disease. Smokers have significantly elevated risks of all-cause mortality and developing a variety of pathological conditions. A direct causal relationship between smoking exposure and the prevalence and the severity of periodontal disease has been firmly established. Although the direct cause for periodontitis is oral bacterial infection, smoking is arguably the strongest behavioral risk factor for the incidence and progression of periodontitis. Smoking has a deleterious effect on all the aspects of periodontium. Smokers have been shown to respond less well to nonsurgical as well as surgical therapy than nonsmokers. Based on this evidence, dental health professionals should advise patients about tobacco's negative health effects as well as the benefits of quitting tobacco use, and tobacco cessation counseling should be a part of the armamentarium of the dental office.